Sistem Pembagian Pendapatanangkutan Kota: Studi Kasus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRAK The research proposed to analysed compensation system that applied in Yogyakarta of public transportation. There are four sample corporations as the object of researched here. There were Kopata, Kobutri, Puskopar, and Aspada. Here is the information you requested from research issued. There are three purposes of this research, those compensation systems, a properly choice systems of compensation, and a responsibility of owner of bus and driver in compilations. Result of research found that the fewer of service issues caused by the bad systems of incomes distributions.